Supraclavicular left neck mass: an unusual presentation of metastatic testicular cancer in two older men - Law, Chinnoi (BMJ Case Rep, 2020)
Two male patients, aged 55 and 75 years, were referred to the ENT and haematology team respectively, with an asymptomatic left supraclavicular neck mass. Investigations revealed metastatic primary testicular seminoma. CT contrast study of the thorax, abdomen and pelvis demonstrated an additional left para-aortic nodal mass in both cases. The initial presentation of a solitary left neck lump from a metastatic testicular seminoma is extremely unusual, especially in an older age group. The pattern of metastatic spread to the supraclavicular neck nodes from a single para-aortic lymph node is also an interesting finding. Although the majority of seminomas present in younger patients in the early stages when confined to the testis, seminoma can also occur in older patients and can present in an atypical manner. The ability to recognise an atypical presentation in an older patient is invaluable for prompt diagnosis, treatment and follow-up of disease. This case also highlights the importance of a multisystematic structured and an open-minded approach to investigating and diagnosing a neck mass.